The impact of US Peace Corps volunteers on the management and leadership of a school in Namibia: a case study - Ipangelwa, Anna (Rhodes University, Faculty of Education, Department of Education, 2003)
Peace Corps Volunteer teachers have played a significant role in Namibia's attempts to restructure education in line with its policy of education for all. While we have learned a great deal in recent years about how Peace Corps Volunteer Teachers have achieved their stated goals and objectives of teaching students and training serving teachers, we still know relatively little about the role they may have played in school management. The purpose of this study is to examine the impact of Peace Corps volunteers work on the management and leadership of the schools they serve. The study focuses on the work of two volunteers based in a combined school in the Ondangwa West educational region of Namibia. The study adopts a qualitative approach and seeks to establish whether there has been an impact by Peace Corps volunteer's work on the management and leadership of this school by focusing on (a) activities performed by Peace Corps volunteers; (b) the experiences of both management and staff in working with Peace Corps volunteers; (c) whether the presence of Peace Corps volunteers that served at the school influence the management and leadership of the school; (d) how the duties and activities performed by these volunteers were perceived by the students, teachers and community. The interview questions that were used to collect data from seven respondents were based on the literature from Peace Corps and the Ministry of Basic Education, Culture and Sport as well as education management and leadership literature. The findings indicate that volunteers that served at this school performed management and leadership related activities with the students, teachers and community and that these activities are having an effect on the management and leadership of the school.
Keywords: Peace Corps (U.S.); Volunteer workers in Education -- Namibia; Education -- Namibia; Education and state -- Namibia; Educational change -- Namibia; School management and organization -- Namibia; Educational leadership -- Namibia